2018
DOI: 10.1186/s12929-018-0404-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of social relationships on Alzheimer’s memory impairment: mechanistic studies

Abstract: Alzheimer’s disease (AD) is characterized by progressive memory and neuronal loss culminating in cognitive impairment that not only affects a person’s living ability but also becomes a society’s as well as a family’s economic burden. AD is the most common form of dementia in older persons. It is expected that the number of people with AD dementia will increase dramatically in the next 30 years, projecting to 75 million in 2030 and 131.5 million in 2050 worldwide. So far, no sufficient evidence is available to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 110 publications
0
71
1
3
Order By: Relevance
“…Social isolation has been shown to be associated with the progression of cognitive deficits, such as in Alzheimer's disease (Donovan et al, 2016), in human and animal models (Hsiao et al, 2018). Thus, the current study may shed light on treatments targeting Rac1 for Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 80%
“…Social isolation has been shown to be associated with the progression of cognitive deficits, such as in Alzheimer's disease (Donovan et al, 2016), in human and animal models (Hsiao et al, 2018). Thus, the current study may shed light on treatments targeting Rac1 for Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 80%
“…1C). It has been reported that one can prevent cognitive decline and delay the onset of dementia by maintaining strong social connections [71,72]. Hsiao et al reviewed the impact of social behaviors on the progression of cognitive deficit in animal models of AD and described a mechanistic scheme that explains how social isolation exacerbates cognitive impairment and how social interaction with conspecifics rescues AD-related memory deficits.…”
Section: Conceivable Effect Of Hearing Interventionconsideration Basementioning
confidence: 99%
“…Other participants were then considered as nonresponders. This was considered in the three study groups because BDNF level is influenced both by physical activity and social interactions [55,56].…”
Section: Complementary Analyses To Identify Determinants Of Plasma Bdmentioning
confidence: 99%